2017
DOI: 10.1007/s41109-017-0033-4
|View full text |Cite
|
Sign up to set email alerts
|

Weighted spectral clustering for water distribution network partitioning

Abstract: In order to improve the management and to better locate water losses, Water Distribution Networks can be physically divided into District Meter Areas (DMAs), inserting hydraulic devices on proper pipes and thus simplifying the control of water budget and pressure regime. Traditionally, the water network division is based on empirical suggestions and on ‘trial and error’ approaches, checking results step by step through hydraulic simulation, and so making it very difficult to apply such approaches to large netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…The first step is clustering, which aims to define the network subsets. Among the various clustering methods are breadth-first search [119], depth-first search [137], K-shortest paths [75], spectrum clustering algorithms [144,145], and multi-level-recursive algorithm [146]. The second step is division, which partitions the network by inserting flow meters or valves.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first step is clustering, which aims to define the network subsets. Among the various clustering methods are breadth-first search [119], depth-first search [137], K-shortest paths [75], spectrum clustering algorithms [144,145], and multi-level-recursive algorithm [146]. The second step is division, which partitions the network by inserting flow meters or valves.…”
mentioning
confidence: 99%
“…The second step is division, which partitions the network by inserting flow meters or valves. Heuristic optimization techniques such as genetic algorithms [145,147] can minimize the economic investment while maximizing the hydraulic performance. Combined resilience metrics reflect the pressure and flow requirements.…”
mentioning
confidence: 99%
“…Kozelj et al [7] presented a case of applying combined weights from two different parameters: pipe diameter and downstream nodal head. Di Nardo et al [8,9] showed that the unweighted spectral partitioning outperformed tested weights for presented case studies by producing solutions with fewer inter-cluster links. The proposed weight cases form previous studies are the following: (unweighted), (pipe diameter), 1⁄ (reciprocal value of pipe length), 5 ⁄ (pipe hydraulic conductance),…”
Section: Methodsmentioning
confidence: 99%
“…Kozelj et al [7] proposed weighted spectral partitioning for DMA design, which also included hydraulic parameters in the partitioning process. Three different weighted spectral clustering methods were compared by Di Nardo et al [8]. Opposing to the previous research, their results go in favour of unweighted partitioning.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation